Literasi Manfaat Program Beasiswa Pendidikan STMA Trisakti - Yohanes Jhony Kurniawan; Heppy Julianto (CV. Ulil Albab Corp, 2024)
This Community Service research is based on the material and non-material benefits of the scholarships, so literacy on the benefits of the educational scholarship program at STMA Trisakti is required. With the existence of literacy on the benefits of the educational scholarship program at STMA Trisakti, it is hoped that there will be an increase in understanding among the community, especially the lower middle class, about alternative financing opportunities with scholarships for those who are the targets of the scholarship. Title as follows;